Prosecuting and defending sexual offence cases - Brown, Daniel; Witkin, Jill (Emond's criminal law series, 2020)
"This book is an update to our best-selling guide to defending and prosecuting a sexual offence case from start to finish. The text weaves strategic information together with an analysis of case law and the relevant provisions of the Criminal Code, integrated in such a way as to serve as a guide through the flow of a sexual offence case. The new edition will incorporate information about the changes flowing from Bill C-51 into the chapters on third party records, other sexual history, and consent. Additionally, it will include new chapters on historical sexual offences and cross-examination on private records."-- Provided by publisher.